An Overview of Nanogel –Novel Drug Delivery System - Jain, Saloni; Ancheria, Rahul Kumar; Shrivastava, Saumya; Soni, Shankar Lal; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Nanogels are innovative drug delivery system that can play an integral part in pointing out many issues related to old and modern courses of treatment such as nonspecific effects and poor stability. Biomedical and pharmaceutical applications of Nanogels have been explored for tissue regeneration, wound healing, surgical device, implantation, and peroral, rectal, vaginal, ocular, and transdermal drug delivery. Nanogels are proficiently internalized by the target cells, avoid accumulating in nontarget tissues thereby lower the therapeutic dosage and minimize harmful side effects. Nanogels may be defined as highly cross linked nano-sized hydrogels ranges from 20-200 nm. They can be administered through various routes, including oral, pulmonary, nasal, parenteral, intra-ocular etc. They have a high degree of drug loading capacity and it shows better permeation capabilities due to smaller size. Nanogels are the novel drug delivery systems for both hydrophilic and hydrophobic drugs.